PENGARUH MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) TERHADAP HASIL BELAJAR DAN BERPIKIR KRITIS SISWA KELAS XI- SMA PADA MATERI ASAM BASA - Melvi Junita Manurung; Elfrida Ginting (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Project Based         Learning (PjBL) model on students' learning outcomes and critical thinking skills, as well as to determine the significant correlation between learning outcomes and students' critical thinking skills. The research was conducted at SMA Negeri 1 Siborong-borong using a quantitative method. The research sample of class XI E as the control class taught using conventional methods, and class XI F taught using the Project Based Learning (PjBL) model. The research instruments consisted of multiple-choice learning outcome tests and essay tests for critical thinking skills. The tests used were hypothesis testing and correlation testing with a significance level of 5% (0.05). The results showed that the average learning outcomes of the experimental class were higher (80.55) compared to the control class (68.75). The average critical thinking skills of students in the experimental class were higher (83.75) compared to the control class (67.11). The result of the first hypothesis test is thitung > ttabel (4.584 > 1.666), indicating that H0 is rejected and Ha is accepted, meaning there is an effect of the PjBL learning model on students' learning outcomes in acid-base material. The result of the second hypothesis test is thitung > ttabel (6.307 > 1.666), indicating that H0 is rejected and Ha is accepted, meaning there is an effect of the PjBL learning model on students' critical thinking skills in acid-base material. And the result of the third hypothesis test (Correlation Test) is rhitung > rtabel (0.3996 > 0.3291), indicating that H0 is rejected and Ha is accepted, meaning there is a significant correlation between learning outcomes and students' critical thinking skills using the PjBL learning model in acid-base material.